1971
DOI: 10.1152/ajplegacy.1971.220.6.1852
|View full text |Cite
|
Sign up to set email alerts
|

Response of lipoprotein lipase in various tissues to cold exposure

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…In this situation, the mobilization of fatty acids from WAT and/or the activation in IBAT of LPL, which is essential for the hydrolysis and distribution of triglyceriderich lipoprotein-associated fatty acids among extrahepatic tissues [38], would be necessary in order to replenish the tissue supply of fatty acids. In fact, several studies have demonstrated that LPL activity is stimulated rapidly in response to cold exposure in IBAT [38][39][40][41][42] but not in EWAT [39,42] or IWAT [38] depots of rodents. In agreement with these reports, in the present study, we have found an increase in LPL mRNA levels in IBAT of lean rats in response to cold exposure, but not in EWAT.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, the mobilization of fatty acids from WAT and/or the activation in IBAT of LPL, which is essential for the hydrolysis and distribution of triglyceriderich lipoprotein-associated fatty acids among extrahepatic tissues [38], would be necessary in order to replenish the tissue supply of fatty acids. In fact, several studies have demonstrated that LPL activity is stimulated rapidly in response to cold exposure in IBAT [38][39][40][41][42] but not in EWAT [39,42] or IWAT [38] depots of rodents. In agreement with these reports, in the present study, we have found an increase in LPL mRNA levels in IBAT of lean rats in response to cold exposure, but not in EWAT.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that cold exposure increases LPL activity in the heart and BAT tissue (25)(26)(27). It has also been shown in piglets exposed to the cold that skeletal muscle LPL activity was increased by 71%, whereas WAT LPL activity was Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Les travaux réalisés sur cette question ont porté sur les effets du jeûne et de la réalimentation (Allman et al, 1965 ;Numa et al, 1961Numa et al, , 1970, sur l'influence de la fré-quence des repas (Chakrabarty et Leveille, 1968Leveille, , 1969, celle de l'heure du repas protéique (Peret et al, 1976a) et celle du taux protéique de la ration (Peret et al, 1976b), sur la comparaison entre apport énergétique à base de glucides ou de lipides (Allred et Roehrig, 1973 ;Bortz et al, 1963 ; Desjardins, 1968Desjardins, , 1969 et enfin sur l'influence de la nature des lipides (Gibson et al,1972 ;Muto et Gibson,1970 Borensztajn et al, 1972 ;Rault et al, 1974 ;Husbands, 1972 ;Shotz et Garfinkel, 1972) Harris, 1975), la nature de l'apport lipidique (Bagdade et al, 1970), la nature de l'apport glucidique (Vrana et al, 1974), l'effet de la température ambiante (Radomski et Orme, 1971).…”
Section: Lipoprotein Lipaseunclassified